Stability study in the performance of sensors and biosensors based on conductor polymers in strong acidic media (2013)
Developing and constructing the mathematical model (applying the linear stability theory and bifurcation analysis), the electrochemical behavior, observed during the work of the CP-based electrochemical sensors and biosensors in strongly acid solution, was investigated. The conditions for the steady-state stability and oscillatory and monotonic instabilities were derived for the work of the biosensor in potentiostatic mode. The results of the analysis for the case of strongly acid solution were compared to the previously obtained for the case of neutral and basic solution and in such way it's possible to make conclusions about the influence of pH on the functioning of sensors and biosensors.